Breast elastography - Barr, Richard G. (Thieme, 2015)
This comprehensive reference covers the principles and techniques used in performing breast elastography, an innovative imaging technology that can dramatically reduce the need for biopsies. The book begins with an introduction of the techniques, followed by sections on how to perform each technique and methods of interpretation, and concludes with more than 60 detailed case studies